Workshop report: Farm-household modelling with a focus on food security, climate change adaptation, risk management and mitigation: a way forward - Wijk, Mark T. van; Rufino, Mariana C.; Thornton, Philip K. (2012)
The workshop entitled: ‘Farm-household modelling with a focus on food security, climate change adaptation, risk management and mitigation: a way forward’ focused on identifying the current strengths and weaknesses of farm and household-level models, and laying out practical pathways to improve these models. This activity followed a recent review on farm household modelling commissioned by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). The workshop took place in Amsterdam, The Netherlands on 23–25 April 2012.